Restriction fragment length polymorphism of the periplasmic flagellar flaA1 gene of Serpulina species. - Fisher, L N (1997)
Forty-one reference and field isolates of intestinal spirochetes representing Serpulina hyodysenteriae, Serpulina innocens, Serpulina pilosicoli, Brachyspira aalborgi, and nonclassified weakly beta-hemolytic intestinal spirochetes were compared by restriction fragment length polymorphism (RFLP) of the periplasmic flagellar (PF) flaA1 gene. Six genetically distinct groups (I through VI), each with a unique RFLP fingerprint pattern, were identified by Southern blotting analysis of EcoRV chromosomal DNA digests with a PCR-amplified digoxigenin-labeled 1-kb fragment of the S. hyodysenteriae isolate B78 PF flaA1 gene. The RFLP fingerprint patterns corresponded to known DNA homology differences between Serpulina species and to provisionally designated species described previously by using phenotypic and genotypic classification schemes. RFLP fingerprinting of the PF flaA1 gene provides a relatively simple genotypic method for identification of intestinal spirochetes without the use of radioisotopes.